THE FORMATION OF THE REGIONS IN RUSSIA IN 2003-2008: THE SCENARIOS OF THE POSITIVE AND NEGATIVE INTEGRATION - Ashikhmina, Y.G. (Perm Federal Research Centre Journal, 2015)
The author analyzes the various scenarios of the positive and negative regional integration in Russia in 2003-2008, considers the examples of the confluence of the complex regions into the single region, the political consequences of the positive and negative integration for the political evolution of Perm Region, Krasnoyarsk Region, Kamchatsky Region, Irkutsk Region and Zabajkalsky Region. The author takes conclusion about the significance of the constructive relations among the federal and regional elite in the process of the integration.